Position choice and swimming costs of juvenile Atlantic salmon salmo salar in turbulent flow. Issue 1 (2nd January 2017) - Wilkes, M.A.; Enders, E.C.; Silva, A.T.; Acreman, M.; Maddock, I.
ABSTRACT: Swimming costs (SCs) for fish have been shown to be affected by turbulence. However, this idea has not yet been implemented in habitat models, which often represent hydraulics using water velocity averaged over time and space. In this study, we analysed the habitat selection of individual juvenile Atlantic salmon Salmo salar (L. 1758) in relation to predicted SC in the turbulent flow of a large outdoor flume. We used a previously published SC model parameterized using mean velocity, turbulence intensity, water temperature and fish mass. Results showed that 86% of fish chose locations with significantly lower predicted SC than expected at random. Position choice was negatively related to predicted SC, mean velocity, spatial velocity gradient, and Reynolds stresses. Based on the findings, a novel habitat suitability curve is recommended for juvenile Atlantic salmon. The results are expected to contribute towards the improvement of bioenergetics modelling to increase our understanding of the impacts of environmental changes and management activities.